1998
DOI: 10.1074/jbc.273.50.33841
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Interaction between Fur and the Iron Transport Promoter of the Virulence Plasmid in Vibrio anguillarum

Abstract: The expression of iron transport genes fatDCBA in Vibrio anguillarum strain 775 is negatively regulated by two iron-responsive repressors, the Fur protein and the antisense RNA, RNA␣. Here we report the identification of the promoter for the iron transport genes and studied the interaction between the V. anguillarum Fur protein and this promoter. The iron transport promoter was localized in a region approximately 300 base pairs upstream of fatD by both primer extension and S1 mapping analysis. High activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 34 publications
2
38
0
Order By: Relevance
“…Furthermore, at least 10 other units very similar to those found in the aerobactin promoter region (Escolar et al, 2000) can be identified upstream of the adhC1 initiation codon. This region also includes the sequence TAGCATTACAT-TATCTATTTTGCT that matches 19 of the 24 nucleotides found in the non-template strand of the Furbinding site I of the promoter region of the fatDCBA operon of the pJM1 plasmid (Chai et al, 1998). The potential regulatory role of these sequences is further supported by the results obtained using S1 mapping, which showed three adjunct adhC1 transcription initiation sites (Fig.…”
Section: Regulation Of the Expression Of Adhcsupporting
confidence: 56%
“…Furthermore, at least 10 other units very similar to those found in the aerobactin promoter region (Escolar et al, 2000) can be identified upstream of the adhC1 initiation codon. This region also includes the sequence TAGCATTACAT-TATCTATTTTGCT that matches 19 of the 24 nucleotides found in the non-template strand of the Furbinding site I of the promoter region of the fatDCBA operon of the pJM1 plasmid (Chai et al, 1998). The potential regulatory role of these sequences is further supported by the results obtained using S1 mapping, which showed three adjunct adhC1 transcription initiation sites (Fig.…”
Section: Regulation Of the Expression Of Adhcsupporting
confidence: 56%
“…A 21-bp Neisseria consensus that shares Ϸ80% homology to the E. coli consensus has been derived and proposed to be the binding sequence of the Neisseria Fur protein (23). Although the 19-and 21-bp consensuses serve as good indicators to identify a Furregulated gene, the Fur-binding sequence identified in the promoters of several Fur-regulated genes differed from the classical Fur-binding sequence (37)(38)(39)(40)(41)(42). In light of these results, the Fur-binding sequence has been reinterpreted to be a combination of three repeats of 6-bp 5Ј-NAT(A͞T)AT-3Ј rather than a 19-bp palindrome (24).…”
Section: Discussionmentioning
confidence: 99%
“…10) are controlled by the concentration of available iron, via at least four plasmid-encoded regulators: two positive regulators, AngR (anguibactin system regulator) and TAF (transacting factor[s]); and two negative regulators, antisense RNA␣ and RNA␤ (19,21,22,25,35,(100)(101)(102)(118)(119)(120)(121). RNA␣ is very stable at high iron concentrations and acts at posttranscriptional level in the repression of fatB and fatA expression, while RNA␤, found under conditions of mild iron limitation, acts on the attenuation of expression of the angR gene in the iron transport-biosynthesis (ITB) operon (19,102 (19,117,133). The promoter for the ITB operon (pITBO) was localized within a region ca.…”
Section: Geneticsmentioning
confidence: 99%
“…In V. anguillarum, Pseudomonas aeruginosa, and other microorganisms, positive regulation by a combination of positive regulatory proteins and the cognate siderophore has also been reported, and the mechanisms are under study (22,26,49,50). Furthermore, it has also been demonstrated in V. anguillarum that negative control of iron uptake gene expression is not only due to repression of transcription initiation by a complex of Fur with iron (19) but also due to posttranscriptional regulation by antisense RNAs acting as a fine-tuning control mechanism (21,26,101). These regulatory strategies enable bacteria, via ironsensing transcriptional activators and repressors, to turn on and off sets of genes that encode proteins for the assembly and export of siderophores and the specific uptake of the ironsiderophore complexes.…”
Section: Introductionmentioning
confidence: 98%